Teaching clinical toxinology in medical schools: The need, challenges and opportunities - Chew, Keng Sheng (Malaysian Medical Association, 2023)
Clinical toxinology is an essential subject that should be included in undergraduate medical curricula. By equipping students with the knowledge and skills to identify and treat venomous animals and use antivenom appropriately reduces the risk of medical negligence and delays in treating and transporting these patients. Unfortunately, given the packed curriculum of undergraduate medical programs, it is important to focus on providing students with essential knowledge and skills to function as competent house officers. Student-centered learning approaches, such as gamification and community service projects, can be effective in enhancing learning and promoting awareness of appropriate toxin-related public measures.